Cloning of the bovine 215-kDa cation-independent mannose 6-phosphate receptor. - Lobel, P (1987)
Four overlapping cDNA clones encoding a partial sequence of the cation-independent 215-kDa mannose 6-phosphate receptor have been identified by screening a fetal calf liver cDNA library with oligonucleotide probes. RNA hybridization analysis showed that the length of the mRNA is approximately 9.5 kilobases. Sequence analysis demonstrated that the clones consist of 4647 contiguous nucleotides and contain an open reading frame coding for a polypeptide of 1461 amino acids, which we estimate represents greater than 75% of the primary structure of the receptor. The deduced amino acid sequence indicates that the receptor has a carboxyl-terminal cytoplasmic domain of 163 amino acids that is rich in acidic residues, a 23-amino acid transmembrane segment, and an extracellular domain containing at least eight homologous repeats of approximately 145 amino acids. One of the repeats contains an additional 43-residue segment that is similar to the type II repeat of fibronectin. Each repeat contains a highly conserved 13-amino acid unit bordered by cysteine residues that may be functionally important.